Antibiotic use in companion animals in veterinary teaching hospitals in Thailand - Sarin Suwanpakdee; Boonrat Chantong; Anuwat Wiratsudakul; Viroj Tangcharoensathien; Angkana Lekagul; Walasinee Sakcamduang (PLoS ONE, 2025)
The high volume of antibiotics used for companion animals, off-label use of human-registered antibiotics for veterinary purposes, and close human-animal interactions raises policy concerns related to antimicrobial resistance in companion animals. This study aimed to assess the volume and type of antibiotic usage in companion animals at veterinary teaching hospitals in Thailand. In 2018, we obtained a dataset of visits that occurred between 2015 and 2017 from eight selected veterinary teaching hospitals with a high caseload of companion animals. In total, we included 938,522 dogs and 242,342 cats in our study. Total antibiotic consumption was estimated, and antibiotic usage was standardized by calculating the amount of antibiotic consumed by weight per year (mg/kg/year). The top five antibiotics used include amoxicillin–clavulanic acid, enrofloxacin, cephalexin, doxycycline, and metronidazole, all of which are commonly used to treat bacterial and parasitic infections. Critically important antimicrobials for human medicine, such as amoxicillin–clavulanic acid and enrofloxacin, were among the most used. From 2015 to 2017, total antibiotic usage (kg) markedly decreased (i.e., by 57.0%), with a particularly notable reduction of 78.2% observed for amoxicillin–clavulanic acid. Moreover, veterinarians’ overall prescriptions of antibiotics registered for human use decreased by 16% over the same period. However, there was a notable increase in the use of injectable antibiotics registered for human use relative to oral forms. Furthermore, we observed a relatively high usage of third-generation cephalosporins, which may contribute to the emergence of antimicrobial resistance in companion animals. This study emphasizes the need to educate veterinarians and veterinary students on the rational use of antibiotics and highlights the importance of regular monitoring and surveillance of antibiotic use in companion animals.